2005
DOI: 10.2165/00002512-200522090-00006
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Treatment of Oesophageal Achalasia in the Old Old and Oldest Old

Abstract: BTX treatment is an effective treatment in a substantial proportion of achalasic patients >80 years of age, in whom benefits are still detectable after 12 months. BTX is a therapeutic option in patients unsuitable for surgery or pneumatic dilatation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Surgeons have reported that Heller myotomy could be more difficult in patients who undergo repeated botulinum toxin A injection, due to increased adhesion of the muscular layer, but, so far, this therapeutic option has to be chosen as a first step in all patients who are eligible for it 31. In contrast, botulinum toxin A is widely demonstrated to be the most effective treatment option in elderly patients or in patients with comorbid illnesses, in whom dilatation or surgery is high-risk 32.…”
Section: Endoscopic Therapiesmentioning
confidence: 99%
“…Surgeons have reported that Heller myotomy could be more difficult in patients who undergo repeated botulinum toxin A injection, due to increased adhesion of the muscular layer, but, so far, this therapeutic option has to be chosen as a first step in all patients who are eligible for it 31. In contrast, botulinum toxin A is widely demonstrated to be the most effective treatment option in elderly patients or in patients with comorbid illnesses, in whom dilatation or surgery is high-risk 32.…”
Section: Endoscopic Therapiesmentioning
confidence: 99%
“…Patients were asked to complete a semistructured questionnaire surveying the presence and frequency of three oesophageal symptoms, namely dysphagia, regurgitation and chest pain, as previously described 18 . A score of 0–3 was attributed to each symptom depending on its occurrence: ‘never’, ‘occasionally’, ‘more than once weekly’ or ‘daily’.…”
Section: Methodsmentioning
confidence: 99%
“…Assessment of oesophageal symptoms was performed at baseline, and at 1 and 2 years after the second injection of BTX (see below). The efficacy of BTX was evaluated on clinical criteria; more specifically, response to treatment was arbitrary defined as a total symptom score of ≤2, whereas a total score of ≥3 was considered suggestive of treatment failure (or relapse) 5, 18, 19 . A barium oesophagogram was performed at baseline in all patients to assess oesophageal diameter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One review looked at 12 frail and elderly patients aged 81-94 years with an American Society of Anaesthesiologists (ASA) class score of III-IV; 100U of botox was injected at two sessions a month apart, patients were followed up for a year and 70% responded symptomatically, albeit to varying degrees. 5 There is a growing enthusiasm to opt straight for a surgical myotomy as the treatment of choice, providing there are no general anaesthetic contraindications. In the elderly patient, most would advocate this approach, with botulinum injections reserved for the frail and those for whom it is contraindicated by frailty or co-morbidity.…”
Section: Oesophageal Dysmotilitymentioning
confidence: 99%